2010
DOI: 10.1126/science.1192698
|View full text |Cite
|
Sign up to set email alerts
|

The Junctional Adhesion Molecule JAML Is a Costimulatory Receptor for Epithelial γδ T Cell Activation

Abstract: Summary Costimulation through Junctional Adhesion Molecule-Like protein interaction with Coxsackie and Adenovirus Receptor mediates epithelial γδ T cell-specific activation and effector function during tissue repair. γδ T cells present in epithelial tissues provide a crucial first line of defence against environmental insults, including infection, trauma and malignancy, yet the molecular events surrounding their activation remain poorly defined. Here we identify an epithelial γδ T cell-specific costimulatory m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
277
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(285 citation statements)
references
References 30 publications
4
277
0
Order By: Relevance
“…Interestingly, monocyte adhesion to the endothelium also induced the formation of transmigratory cups enriched in p120, providing further evidence for the expression of junctional proteins by leukocytes11 and emphasizing the role of p120 as an intracellular mediator of monocyte migration 12. In addition, JAML expression on myeloid and CD8 T cells populations within the CNS is an important aspect that warrants further investigation as JAML is also a costimulatory molecule able to support cell activation and effector functions 13. The migration of neutrophils and monocytes across epithelium and EC lines was shown to be decreased when JAML is blocked 4, 14.…”
Section: Discussionmentioning
confidence: 77%
“…Interestingly, monocyte adhesion to the endothelium also induced the formation of transmigratory cups enriched in p120, providing further evidence for the expression of junctional proteins by leukocytes11 and emphasizing the role of p120 as an intracellular mediator of monocyte migration 12. In addition, JAML expression on myeloid and CD8 T cells populations within the CNS is an important aspect that warrants further investigation as JAML is also a costimulatory molecule able to support cell activation and effector functions 13. The migration of neutrophils and monocytes across epithelium and EC lines was shown to be decreased when JAML is blocked 4, 14.…”
Section: Discussionmentioning
confidence: 77%
“…82 These results appear at odds with other reports of JAML-CAR interactions facilitating T-cellemediated wound healing in the skin of mice. 83 However, in those studies, prorestitutive signals were derived downstream of from T-cell expressed JAML, whereas the inhibitory signals during transepithelial migration of neutrophils were derived downstream of epithelial expressed CAR. These observations suggest that bidirectional signals emanating from JAML-CAR interactions mediate complex effects on epithelial function through direct and indirect mechanisms.…”
Section: Neutrophils Engage Basolateral Epithelial Receptors During Tmentioning
confidence: 96%
“…67 In addition to the conventional costimulators that are shared with ab-T cells, several novel molecules can serve as the secondary signals for the activation of cd-T cells. It has been found that the expression of junctional adhesion molecule-like protein 68 and high-mobility group box 1 69 by cd-T cells provides positive signals for the activation of cd-T cells, whereas stimulation with E-cadherin downregulates their functions. 70 The natural killer (NK) cell receptor family is another important group of costimulators for regulating the activity of cd-T cells, and the balance among stimulatory and inhibitory natural killer WW (NK) cell receptor signals might determine the functions of cd-T cells.…”
Section: Host Cell-derived Signalsmentioning
confidence: 99%